SYSTEMATIC LITERATURE REVIEW: FAKTOR-FAKTOR PENENTU MOTIVASI BELAJAR SISWA DALAM PENDIDIKAN VOKASI OTOMOTIF - Fadhil Novriandi Pratama; Muslim Muslim; Wagino Wagino; Toto Sugiarto (Ensiklopedia Research and Community Service Review, 2026)
Abstract: This study aims to synthesize the determinants of learning motivation of automotive vocational students towards the Industrial 5.0 era. Using the Systematic Literature Review (SLR) method based on the PRISMA protocol, this study screened the last five years of empirical articles from the Scopus, Web of Science, and Google Scholar databases, which were then tested for quality using CASP instruments before being analyzed thematically, hybridly. Key findings suggest that the integration of Extended Reality (VR, AR, MR) technology has a much greater impact in triggering students' intrinsic motivation than traditional economic incentives, as it acts as a visual scaffolding that reduces the spatial cognitive load and presents psychomotor safety that eliminates motor anxiety through a space of "productive failure". The novelty of this research lies in the formulation of the "Automotive Vocational Motivation Ecological Model" which isolates the immersive ecosystem as an instrument for mitigating emotional saturation, not just a tool to boost cognitive value. Scientifically, this study contributes to expanding Self-Determination Theory and Social Cognitive Career Theory in the engineering environment, while practically providing a blueprint for TVET managers to synergize workshop hardware upgrades with teachers' adaptive instruction to erode negative stigma and produce graduates who master digital literacy and Industry 5.0 interpersonal skills. Keywords: Automotive Vocational Education, Learning Motivation, Immersive Technology, Extended Reality, Psychomotor Safety.